92.1k views
3 votes
Galena is solving the following system. 3x+2y+3z =5 7x+y +7z=-1 4x-4y-z=-3

Step 1 she multiplies equation (3) by 3 and adds it to equation (1)
Step 2 She multiplies equation (3) by -7 and adds it to equation (2)
which statement explains Galena’s mistake?
1 she adds equation 1 instead of equation 2 in step 1
2 She does not multiply equation 3 in step 1 by the correct value
3 She did not multiply equation 3 in step 2 by the correct value
4 she added equation 2 instead of equation 1 in step 2

User Splatbang
by
5.5k points

2 Answers

3 votes

Answer:

She did not multiply equation 3 in step 2 by the correct value.

Explanation:

User Johann
by
4.8k points
3 votes

Answer:

She did not multiply equation 3 in step 2 by the correct value.

Explanation:

Given:


3x+2y+3z=5\\7x+y+7z=-1\\4x-4y-z=-3

In order to solve this, we need to eliminate any one variable and then form a simultaneous equation with the remaining two variables. Then, we nee to solve the simultaneous equation.

Here, Galena is trying to eliminate the variable
z first.

Step 1: She multiplies equation (3) by 3 and adds it to equation (1)

Let us multiply equation (3) by 3


(4x-4y-z=-3)* 3 = (3* 4x)-(3* 4y)-(3* z)=3* -3\\(4x-4y-z=-3)* 3 =12x-12y-3z=-9

Now, adding this to equation 1 will cancel out z terms.


12x-12y-3z+3x+2y+3z=-9+5\\(12x+3x)+(-12y+2y)+(3z-3z)=-4\\15x-10y+0=-4

Now, she need to make one more equation in
x\ and \ y.

Step 2: She multiplies equation (3) by -7 and adds it to equation (2)

Multiplying equation (3) by -7 will give,


(4x-4y-z=-3)* -7 = (-7* 4x)-(-7* 4y)-(-7* z)=-7* -3\\(4x-4y-z=-3)* 3 =-28x+28y+7z=21

Now, adding this to equation 2 will not cancel out z terms.


-28x+28y+7z+7x+y+7z=21-1\\(-28x+7x)+(28y+y)+(7z+7z)=20\\-21x+29y+14z=20

So, she makes mistake in step 2 as the
z terms are not being cancelled.

User CalebHC
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.